Bis(trifluoromethanesulfonimide) (BSI): Acidity and application to hydrofunctionalization as a Brønsted acid catalyst. (9th April 2021) - Takagi, Ryukichi; Sakai, Yuichiro; Duong, Duyen Thi
Abstract: A binaphthyl derivative, bearing bis(trifluoromethanesulfonimide) (BSI) moiety, was developed as a novel Brønsted acid. Computational prediction of the p K a value of BSI indicated its classification as a strong Brønsted acid. BSI catalyzed the hydroamination of alkenyl amines in hexafluoroisopropanol (HFIP) with efficiency comparable to that of TsOH∙H2 O, Tf2 NH, and TfOH. The adjacent sulfonimide groups on BSI were important for enhancing acidity. BSI additionally catalyzed the hydroalkoxylation of alkenyl alcohols in HFIP with high efficiency. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Leave this area blank for abstract info. Image 1 Highlights: A binaphthyl derivative, bearing bis(trifluoromethanesulfonimide) (BSI) moiety, was developed as a novel Brønsted acid. Computational prediction of the p K a value of BSI indicated its classification as a strong Brønsted acid. BSI catalyzed the hydroamination of alkenyl amines in HFIP with efficiency comparable to that of TsOH∙H2 O, Tf2 NH, and TfOH.